2018
DOI: 10.3758/s13415-018-0562-z
|View full text |Cite
|
Sign up to set email alerts
|

Visual awareness negativity is an early neural correlate of awareness: A preregistered study with two Gabor sizes

Abstract: Electrophysiological recordings are commonly used to study the neural correlates of consciousness in humans. Previous research is inconsistent as to whether awareness can be indexed with visual awareness negativity (VAN) at about 200 ms or if it occurs later. The present study was preregistered with two main aims: First, to provide independent evidence for or against the presence of VAN, and second, to study whether stimulus size may account for the inconsistent findings. Subjects were shown low-contrast Gauss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 37 publications
(90 reference statements)
6
28
0
Order By: Relevance
“…Thus, our results suggest that VAN correlates with visual awareness. Our finding was consistent with previous studies (Wilenius-emet et al, 2004; Rutiku et al, 2015; Koivisto and Grassini, 2016; Eklund and Wiens, 2018), which suggested that VAN was an early electrophysiological correlate of visual awareness.…”
Section: Discussionsupporting
confidence: 94%
“…Thus, our results suggest that VAN correlates with visual awareness. Our finding was consistent with previous studies (Wilenius-emet et al, 2004; Rutiku et al, 2015; Koivisto and Grassini, 2016; Eklund and Wiens, 2018), which suggested that VAN was an early electrophysiological correlate of visual awareness.…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, there was a significant N2 difference between aware and unaware trials over posterior temporal and occipital electrodes. According previous studies (e.g., Wilenius-emet et al, 2004; Rutiku et al, 2015; Koivisto et al, 2016; Koivisto and Grassini, 2016; Eklund and Wiens, 2018), this significant negative amplitude difference between aware and unaware conditions in N1–N2 latency range over posterior temporal and occipital electrodes is commonly known as VAN. With respect to VAN, our result is somewhat different from previous null results (Lamy et al, 2009; Salti et al, 2012).…”
Section: Discussionmentioning
confidence: 77%
“…VAN is the negative amplitude difference between aware and unaware conditions (Koivisto and Revonsuo, 2010; Railo et al, 2011). It typically appears around 200 ms (N1–N2 latency range or N200) in posterior temporal and occipital electrodes (Railo et al, 2011; Koivisto et al, 2016, 2017; Koivisto and Grassini, 2016; Eklund and Wiens, 2018). LP is the positive amplitude difference between aware and unaware condition in the P3 time window (Koivisto and Revonsuo, 2010; Railo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Mainly, they can be classified as “early” or “late” theories of visual awareness depending on the temporal window considered to be critical for the emergence of awareness. Some studies have identified VAN as the earliest neural marker of visual awareness, fueling the idea that LP is more related to further post-perceptual processing rather than to conscious perception per se (Koivisto and Revonsuo, 2003 , 2010 ; Wilenius-Emet et al, 2004 ; Pitts et al, 2014 ; Koivisto and Grassini, 2016 ; Koivisto et al, 2016 ; Eklund and Wiens, 2018 ; Mazzi et al, 2019 ; Ye and Lyu, 2019 ). Other evidence flowing into the late theories of visual awareness, usually endorsing the global workspace theory as well, have indicated that LP, instead, could represent the ERP component giving rise to conscious perception (Sergent et al, 2005 ; Babiloni et al, 2006 ; Del Cul et al, 2007 ; Lamy et al, 2009 ; Dehaene and Changeux, 2011 ; Salti et al, 2012 ; Boncompte and Cosmelli, 2018 ).…”
Section: Discussionmentioning
confidence: 99%